MATERNAL ROLE CONFIDENCE: CONCEPT PAPER - Mugadza, Gladys; Longwe, Rachael; Njanje, Agness; Zvinavashe, Mathilda; Haruzivishe, Clara; Rukweza, Judith (IJRDO- Journal of Educational Research, 2017)
The purpose of this concept paper was to determine a concept analysis on Maternal RoleConfidence of during the early postpartum period. A concept analysis using Walker &Avantiwas done. Eight articles were systematically reviewed to define and clarify maternal roleconfidence. The following search engines were used as data sources: google scholar, PubMed,Biomed central and www.opendoar.org. Attributes of maternal role confidence include thefollowing, maternal intrinsic role, ask for help, and identifying baby cues. The attributes wereidentified to standardize care. Despite the dynamic nature of maternal role confidence, theprovided definition of maternal role confidence facilitate a clearer understanding of whatmaternal role confidence is.